The Illusory World of a Peculiar Man: A Psychoanalytical Study of Nicholai Gogolâ€™s â€œDiary of a Madmanâ€ - Sayyed Rahim Moosavinia; Ala Bavarsad (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2018)
To become clear, the concept of madness, the hows and whys that follows the recognition of it needs a discerning view. Thereupon, this research is going to study the madness of the main character of the short story â€œDiary of a Madmanâ€ written by Nikolai Gogol in which he meticulously illustrates how a madmanâ€™s mind operates. A pivotal concept to be dealt with is the power of unconscious, which according to Sigmund Freud has a considerable influence on the psychic system. Freud maintains that if the Ego is not able to keep a balance between its demands and the unconscious desires, Psychosis happens. In madmanâ€™s case, it is Schizophrenia. The madman shows abnormalities like hallucinations, delusions, disorganized speech and disorganized behavior which are all symptoms of schizophrenia. Each symptom will be discussed in detail through the study. Another issue which is worth being elucidated is the madmanâ€™s place in Lacanian Orders. Jacques Lacan depicts psycheâ€™s development in three orders or phases: The Real, the Imaginary, and the Symbolic. In this research the focus will be on the imaginary order as the madman shows signs of being stuck in this phase without any positive movement toward the next, the symbolic. According to Lacan, psychosis is the consequence of the incapability in entering the symbolic order. Accordingly, this research will study the madmanâ€™s psychosis and his situation in the psychic world.